2010
DOI: 10.1677/erc-09-0340
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and molecular crosstalk between leptin receptor and estrogen receptor-α in breast cancer: molecular basis for a novel therapeutic setting

Abstract: Obesity is associated with an increased risk of breast cancer. A number of adipocytokines are increased in obesity causing low-level chronic inflammation associated with an increased risk of tumors. The adipocytokine leptin shows profound anti-obesity and pro-inflammatory activities. We have hypothesized that in common obesity, high circulating leptin levels might contribute to an increased risk of breast cancer by affecting mammary cell proliferation and survival. Leptin exerts its activity not only through l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 27 publications
5
51
0
Order By: Relevance
“…A study showed that inhibition of leptin receptor by siRNA leads to down-regulation of ERα gene expression (Fusco et al, 2010). Thus, modulation of each involving gene (leptin, leptin receptors, ER) can cause interference in the entire pathway in ER+ cells and based on these mechanisms, the synergistic inhibitory effects of curcumin and silibinin on leptin expression are, therefore, due to their effects on the same targets.…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that inhibition of leptin receptor by siRNA leads to down-regulation of ERα gene expression (Fusco et al, 2010). Thus, modulation of each involving gene (leptin, leptin receptors, ER) can cause interference in the entire pathway in ER+ cells and based on these mechanisms, the synergistic inhibitory effects of curcumin and silibinin on leptin expression are, therefore, due to their effects on the same targets.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive accumulation of visceral adipose tissues in humans is associated with various chronic diseases, including type II diabetes, high blood pressure, hypertension, dyslipidemia, various types of cancer and cardiovascular diseases (5,6). Evidence has suggested that the excessive accumulation of adipose tissue alters the secretion of adipokines, including leptin, interleukin (IL)-6, resistin, CCL2, adiponectin and tumour necrosis factor (TNF)-α, which promote proliferation, angiogenesis and invasion in certain types of cancer (7).…”
Section: Introductionmentioning
confidence: 99%
“…The hormone can also increase the invasiveness and metastatic potential of BC cells [15], and promote angiogenesis while maintaining a microenvironment favorable for BC development [16]. Furthermore, leptin is known to crosstalk with and transactivate several pathways that are targets for BC therapy, including the estrogen, EGF receptor and HER2 pathways [13,17,18]. Consequently, in recent years the leptin/ObR system has emerged as a new and promising target in BC therapy [13,19].…”
Section: Themed Article Y Breast Cancermentioning
confidence: 99%